2005
DOI: 10.1557/jmr.2005.0207
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Crystal Orientation and In-plane Alignment of La-doped YBCO Thin Film on BaZrO3-buffered MgO Substrate

Abstract: Y 0.9 Ba 1.9 La 0.2 Cu 3 O y (La-YBCO) thin films were prepared by an off-axis magnetron sputtering method on MgO substrates with and without a BaZrO 3 buffer layer. Insertion of BaZrO 3 buffer layer was effective for obtaining La-YBCO films with pure c-axis orientation and in-plane alignment at low temperatures below 600°C. We prepared La-YBCO thin films on BaZrO 3 -buffered MgO substrates using a temperature-gradient method, in which a template La-YBCO layer was first deposited at 600°C, and then the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They pointed out that the reduced interfacial energy between SmBCO and BZO by joint with common Ba-O bonds improved the crystal orientation of SmBCO films. Our preliminary experiments indicated that the insertion of the BZO-buffer was also effective to preprare c-axis-oriented La-YBCO thin films [10]. In this work, we demonstrate the effective utilization of the BZO-buffer to prepare purely c-axis-oriented La-YBCO films on MgO substrates using the hollow-body holder.…”
Section: Introductionmentioning
confidence: 77%
“…They pointed out that the reduced interfacial energy between SmBCO and BZO by joint with common Ba-O bonds improved the crystal orientation of SmBCO films. Our preliminary experiments indicated that the insertion of the BZO-buffer was also effective to preprare c-axis-oriented La-YBCO thin films [10]. In this work, we demonstrate the effective utilization of the BZO-buffer to prepare purely c-axis-oriented La-YBCO films on MgO substrates using the hollow-body holder.…”
Section: Introductionmentioning
confidence: 77%
“…The process contains oxide film deposition, patterning by a conventional photolithography, ion-beam etching, and ashing for photoresist removal. A 200-nm-thick (La-YBCO) film deposited by off-axis dc magnetron sputtering on an MgO (100) substrate with a buffer was used for the ground plane [15]. A 250-nm-thick (100) film was deposited on the La-YBCO by off-axis rf magnetron sputtering for an insulating layer.…”
Section: Methodsmentioning
confidence: 99%